Genome-wide analysis reveals differential selection involved with copy number variation in diverse Chinese Cattle. Issue 1 (December 2017) - Yang, Liu; Xu, Lingyang; Zhu, Bo; Niu, Hong; Zhang, Wengang; Miao, Jian; Shi, Xinping; Zhang, Ming; Chen, Yan; Zhang, Lupei; Gao, Xue; Gao, Huijiang; et al.
Abstract Copy number variations (CNVs) are defined as deletions, insertions, and duplications between two individuals of a species. To investigate the diversity and population-genetic properties of CNVs and their diverse selection patterns, we performed a genome-wide CNV analysis using high density SNP array in Chinese native cattle. In this study, we detected a total of 13, 225 CNV events and 3, 356 CNV regions (CNVRs), overlapping with 1, 522 annotated genes. Among them, approximately 71.43 Mb of novel CNVRs were detected in the Chinese cattle population for the first time, representing the unique genomic resources in cattle. A newV i statistic was proposed to estimate the region-specific divergence in CNVR for each group based on unbiased estimates of pairwiseV ST . We obtained 12 and 62 candidate CNVRs at the top 1% and top 5% of genome-wideV i value thresholds for each of four groups (North, Northwest, Southwest and South). Moreover, we identified many lineage-differentiated CNV genes across four groups, which were associated with several important molecular functions and biological processes, including metabolic process, response to stimulus, immune system, and others. Our findings provide some insights into understanding lineage-differentiated CNVs under divergent selection in the Chinese native cattle.